Szlachta dawnego księstwa głogowskiego według tablic wasalnych z 1752 r. = The gentry of the historic Duchy of Głogów according to vassal plaques from 1752 - Konopnicka, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The plaques are the significant source in defining the socio-political structure of the Silesian gentry. They allow among others to create a map of gentry estates, the type and level of engagement of this group in public life of the Prussian country or they say about its activity beyond the borders of monarchy. They are the basic aid in defining ways of noble career in Prussian reality.
Keywords: Księstwo Głogowskie - historia; szlachta śląska; spis; źródła historyczne; 18 w.